Causal effects of post-traumatic stress disorder on autoimmune thyroid disease: insights from mendelian randomization - Chen, Zhaorong; Yu, Yunfeng; Yao, Jiayu; Guo, Zirui; Cui, Yanhui; Li, Fang; Li, Changqi (Frontiers in Psychiatry, 2024)
The relationship between post-traumatic stress disorder (PTSD) and autoimmune thyroid disease (AITD) needs further evaluation. This study employs Mendelian randomization (MR) to investigate the causal correlations of PTSD with autoimmune thyroiditis (AIT) and Graves' disease (GD).Methods: Datasets for PTSD, AIT, and GD were obtained from FinnGen. The exposure-outcome causal relationship was assessed using inverse variance weighted, MR-Egger, and weighted median. Horizontal pleiotropy was evaluated through the MR-Egger intercept, heterogeneity was examined using Cochran's Q test, and robustness was assessed via leave-one-out sensitivity analysis.Results: MR analysis indicated no significant causal relationship between PTSD and AIT (OR 0.920, 95% CI 0.832 to 1.017, p = 0.103), but a potential increase in the risk of GD associated with PTSD (OR 1.056, 95% CI 1.008 to 1.105, p = 0.021). MR-Egger intercept showed no horizontal pleiotropy (p > 0.05), and Cochran's Q showed no heterogeneity (p > 0.05). Sensitivity analysis suggested the MR results were robust.Evidence of an MR association between genetic liability to PTSD and an increased risk of GD were provided, but no evidence of association between PTSD and AIT. The findings indicate that individuals with PTSD may have an increased likelihood of developing GD, underscoring the importance of further research to comprehend the intricate interplay between PTSD and thyroid disorders.